BADIUZZAMAN SAID NURSI'S PERSPECTIVE ON THE NEO-TASAWWUF ISSUE OF RISALE-I NUR IN URBAN MUSLIM SOCIETY - Prayogo, Tonny Ilham; Yusron, Saidil; Saleh, Sujiat Zubaidi; Mulyana, Agus; Muhajir, Muhammad Arif (AKADEMIKA: Jurnal Pemikiran Islam, 2024)
Tasawwuf is a part of the study that can explore mysticism in life to get nearer to God. The modern era has disrupted the essence of the role of religion and metaphysics to be something more material and substantial. As a consequence, there is a development of Islam with socio-moral reconstruction of urban society which is called neo-Sufism. The aim of this research is to see how Sa'id Nursi tried with his 'Aql (intellect) and Qalb (heart) to comprehend the al-Qur'an in order for human beings to reach the haqiqi (ultimate) truth. The type of this research is literature research (library research). In this regard, it is more focused on studying, analyzing, researching, and understanding the renewal of Sufism in the book of Kulliyyat Risale-I Nur. A thematic approach is also employed in interpreting Sa'id Nursi's Sufism. The finding in this study is that Said Nursi had provide neo-Sufism in tasawwuf is by making nature as a mediator between man and God by including an element of fikr between dzikr and shukr, where the other Sufis only use dzikr and shukr without fikr, for achieving makrifatullah. Also, it provides a reformation of Sa'id Nursi's tasawwuf in relation to the contextual-conditional factors and the spiritual aridity of twentieth-century urban Moslem society. Therefore, this neo-Tasawwuf could potentially serve a more positive functional role in contemporary society in all aspects.